COMPARACIÓN DE LA OSTEOLOGÍA DE LA SALAMANDRA Bolitoglossa adspersa (URODELA:PLETHODONTIDAE) CON OTROS URODELOS - Restrepo, Ana Eugenia; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
The discussion of the distinguishing features of the osteology of the plethodontid salamander BolittJglossa adspersa from the Chingaza National Natural Park is given. This work is part of an osteologycal and myological study wich has been done with twenty-five specimens. For obtaining dry skeletons of one male and one fe,ale, the technique described by SIMMONS (1986) was followed. Twelve specimens were diferentially stained for bone and cartilage following the procedura described by DINGERKUS & UHLER (1977). The fussion of the tll.fsus (1+2+3) was observed, contrary to whatis found in otherpapers, in wich is reported that the fussion is between tarsus (3+4+5).